Pengaruh Keadilan, Kualitas Layanan Dan Kemungkinan Terdeteksinya Kecurangan Terhadap Persepsi Wajib Pajak Mengenai Etika Penggelapan Pajak (Tax Evasion) - Fauziah, Fatihah (Jurnal Akuntansi UMMI, 2021)
ABSTRACT This study purposed to determine the fairness, quality of service and the possibility of fraud detection the taxpayer's perception of the ethics of tax evasion. Technical data retrieval is by distributing a questionnaire to taxpayers, samples are incidental sampling, the number of samples in this study were 100 people on the taxpayer STO Sukabumi. The analysis used is multiple linear regression. The analysis used  is multiple linear regression. This analysis is used to determine the partial significant, coefficient of determination test and t test Simple linear regression test results obtained Ŷ = 1.372 + 0.021 X - 0.008 X2 + 1.040 X3 From the regression equation, it can be seen that the intercept coefficient of 1.372 implies that when the level of fairness, quality of service and the possibility of fraud detection (X1X2X3) fixed, then the rate of tax evasion ethics (Y) is equal to 1.372. Determinant coefficient test showed the value 96.80%. The results of the t test for variables Fairness 0.830 <1.66 t table with 0.409 significant level, this shows that the fairness had no effect on the ethics of tax evasion. While the results of the t test for variables quality of service -0.603 < 1.66 t table with 0.548 significant level, this shows that the quality of service had no effect on the ethics of tax evasion. results of the t test variables the possibility of fraud detection 49.652 > 1.66 t table with 0.00 significant level, this shows that the possibility of fraud detection effect significantly to the ethics of tax evasion